Group Decision and Negotiation. A Socio-Technical Perspective : 17th International Conference, GDN 2017, Stuttgart, Germany, August 14-18, 2017, Proceedings /: 17th International Conference, GDN 2017, Stuttgart, Germany, August 14-18, 2017, Proceedings. (2017) - Unknown
No abstract available